Analisis Implementasi Strategi Pemasaran Asuransi Pendidikan Mitra Iqra Plus Dalam Kajian Asuransi Syariah - Atika Andriani; Sri Ramadhani; Rahmat Daim Harahap (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Mitra Iqra Plus is one of the products owned by PT. Bumiputera Sharia Life Insurance, KPS Medan, which aims to help fund children's education. The purpose of this study was to determine the implementation of Mitra Iqra Plus' educational insurance marketing strategy in the study of sharia insurance at PT Asuransi Jiwa Syariah Bumiputera, KPS Medan, the application of sharia principles in the marketing implementation of Life Insurance products at PT Asuransi Jiwa Syariah Bumiputera, KPS Medan, and challenges in implementing sharia. marketing conducted by PT Asuransi Jiwa Syariah Bumiputera, KPS Medan. This type of research uses qualitative research. Data collection techniques in the form of interviews, observations, and documentation. The data analysis technique used is to reduce the data, present the data, then draw conclusions. The results show that PT Asuransi Jiwa Syariah Bumiputera, KPS Medan implements according to sharia marketing principles ranging from Wisdom (Strategy), Needs (Needs), Halal (Tayyibat), Welfare (Falah), Mutual Consent. The inhibiting factors in implementing the Mitra Iqra Plus educational insurance marketing strategy are the lack of public knowledge about sharia insurance, lack of public trust in sharia insurance, lack of agents and customers who are difficult to collect for premium payments. The challenge is the lack of technology development, the weak market share of PT. AJS Bumiputera due to lack of support from the government and the community. Keywords: Implementation of Sharia Marketing Strategy, Mitra Iqra Plus, Sharia Insurance.